2006
DOI: 10.1038/nature04625
|View full text |Cite
|
Sign up to set email alerts
|

An unconventional myosin in Drosophila reverses the default handedness in visceral organs

Abstract: The internal organs of animals often have left-right asymmetry. Although the formation of the anterior-posterior and dorsal-ventral axes in Drosophila is well understood, left-right asymmetry has not been extensively studied. Here we find that the handedness of the embryonic gut and the adult gut and testes is reversed (not randomized) in viable and fertile homozygous Myo31DF mutants. Myo31DF encodes an unconventional myosin, Drosophila MyoIA (also referred to as MyoID in mammals; refs 3, 4), and is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
327
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(336 citation statements)
references
References 29 publications
8
327
1
Order By: Relevance
“…LR asymmetry is established in some animals during early developmental stages, long before cilia are present or in some cases, with no cilia present at all; these include snails (Meshcheryakov and Beloussov, 1975;Shibazaki et al, 2004), sea urchin (Kitazawa and Amemiya, 2007), Drosophila (Hozumi et al, 2006;Coutelis et al, 2008), Arabidopsis (Hashimoto, 2002;Thitamadee et al, 2002;Abe et al, 2004), and C. elegans (Priess, 1994;Hutter and Schnabel, 1995), for example. Other animals establish the LR axis later in development, when thousands of cells are present, but also without using cilia.…”
Section: Many Phyla Establish Lr Asymmetry Without Ciliary Flowsmentioning
confidence: 99%
“…LR asymmetry is established in some animals during early developmental stages, long before cilia are present or in some cases, with no cilia present at all; these include snails (Meshcheryakov and Beloussov, 1975;Shibazaki et al, 2004), sea urchin (Kitazawa and Amemiya, 2007), Drosophila (Hozumi et al, 2006;Coutelis et al, 2008), Arabidopsis (Hashimoto, 2002;Thitamadee et al, 2002;Abe et al, 2004), and C. elegans (Priess, 1994;Hutter and Schnabel, 1995), for example. Other animals establish the LR axis later in development, when thousands of cells are present, but also without using cilia.…”
Section: Many Phyla Establish Lr Asymmetry Without Ciliary Flowsmentioning
confidence: 99%
“…The use of isolated F-actin binding domains from proteins such as moesin or fimbrim [Edwards et al, 1997;Sheahan et al, 2004] has the potential to overcome this problem, but in general, the properties of a given F-actin binding protein or domain used for in vivo F-actin labeling have not been characterized with respect to their effects on F-actin stability. Further, in some cases, such constructs have been reported to alter actin-dependent processes in vivo [Hozumi et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that Myo95E 1 and Myo95E 2 are null alleles of Myo95E. We used the Myo95E 1 allele in subsequent studies, because it had a larger deletion than Myo95E 2 ( Figure 1C).Myo31DF or Myo61F homozygous mutant flies were previously reported to be viable and fertile (Hozumi et al 2006;Speder et al 2006;Hegan et al 2007). Our finding that the Myo61F 1 or Myo95E 1 homozygotes were also viable and fertile (data not shown) combined with the earlier data suggests that all class I myosins are dispensable for survival in Drosophila, if their functions are disrupted separately.…”
mentioning
confidence: 99%
“…These results demonstrated that class I myosins are not essential for survival itself, but are required for optimal hatching and survival rates, and thus are important mediators in Drosophila, at least under our experimental conditions. Differential expression of Myo31DF, Myo61F, and Myo95E during embryogenesis Myo31DF and Myo61F mRNAs and their protein products are detected in the gut epithelium and genital disc (Morgan et al 1995;Hozumi et al 2006;Speder et al 2006;Petzoldt et al 2012). To gain insight into the tissue-specific roles and functional redundancy of the three class I myosins in the LR asymmetric development of the embryonic gut, we analyzed their expression in embryos, using in situ hybridization.…”
mentioning
confidence: 99%